Faktor-Faktor yang Mempengaruhi Penghentian Prematur Prosedur Audit pada BPK-RI Perwakilan Propinsi Jawa Tengah - Atiqoh, Dewi Nurul; Nurdhiana, Nurdhiana (STIE Widya Manggala, 2013)
The objective of this research was to analyze Time Pressure, Audit Risk, Materiality, Review Procedures and Quality Control that could affect the Premature Sign-Off Audit Procedures on BPK-RI Representative of Central Java Province. The populations of this research were 66 auditors who have worked for BPK-RI Representative Central Java Province. Meanwhile the samples of this research were 57 auditors who have worked for BPK-RI Representative of Central Java Province. The sampling technique used was non probability with cencus technique. The analysis technique used was multiple liniear regression. The result of this research has shown that variable of Time Pressure had negative effect on Premature Sign-Off Audit Procedures. Audit Risk had negative effect on Premature Sign-Off Audit Procedures. Materiality had positive effect on Premature Sign-Off Audit Procedures. Review Procedures and Quality Control had positive effect on Premature Sign-Off Audit Procedures. The result simultaneously showed that there was significant effect of Time Pressure, Audit Risk, Materiality, Review Procedures and Quality Control on Premature Sign-Off Audit Procedures by 99,8%, while remaining 0,2% influenced by other variable beyond the variables examined.